Jual beli dalam Al-Qur’an dan hadist melalui pendekatan tafsir Maudhu’i - Nisa’, Isma Mutia Khoirun (Maliki Interdisciplinary Journal, 2026)
Buying and selling is a form of transaction that plays a central role in the economic life of Muslims. In the Quran, buying and selling is legally permissible under certain pillars and conditions. The Quran and Hadith provide a strong normative foundation regarding the permissibility, principles, and ethics of buying and selling transactions to avoid harmful practices such as usury, fraud, and injustice. This article aims to examine the concept of buying and selling in the Quran and Hadith through a thematic tafsir approach, compiling and analyzing verses and hadith related to buying and selling and financial management. The research method used is qualitative research based on library research, with the primary sources being the Quran, Hadith, and classical and contemporary tafsir literature. The results of the study indicate that buying and selling in Islam is permissible as long as it meets the principles of willingness, honesty, justice, trustworthiness, and freedom from usury and gharar. The maudhu’i interpretation approach allows for a comprehensive and systematic understanding of Islamic economic values, making them relevant for application in modern economic practices, including digital trade and Islamic finance.